Risk Factors and Attack Rates of Seasonal Influenza Infection: Results of the Southern Hemisphere Influenza and Vaccine Effectiveness Research and Surveillance (SHIVERS) Seroepidemiologic Cohort Study. (17th July 2018) - Huang, Q Sue; Bandaranayake, Don; Wood, Tim; Newbern, E Claire; Seeds, Ruth; Ralston, Jacqui; Waite, Ben; Bissielo, Ange; Prasad, Namrata; Todd, Angela; Jelley, Lauren; Gunn, Wendy; et al.
Abstract: Background: Understanding the attack rate of influenza infection and the proportion who become ill by risk group is key to implementing prevention measures. While population-based studies of antihemagglutinin antibody responses have been described previously, studies examining both antihemagglutinin and antineuraminidase antibodies are lacking. Methods: In 2015, we conducted a seroepidemiologic cohort study of individuals randomly selected from a population in New Zealand. We tested paired sera for hemagglutination inhibition (HAI) or neuraminidase inhibition (NAI) titers for seroconversion. We followed participants weekly and performed influenza polymerase chain reaction (PCR) for those reporting influenza-like illness (ILI). Results: Influenza infection (either HAI or NAI seroconversion) was found in 321 (35% [95% confidence interval, 32%–38%]) of 911 unvaccinated participants, of whom 100 (31%) seroconverted to NAI alone. Young children and Pacific peoples experienced the highest influenza infection attack rates, but overall only a quarter of all infected reported influenza PCR–confirmed ILI, and one-quarter of these sought medical attention. Seroconversion to NAI alone was higher among children aged <5 years vs those aged ≥5 years (14% vs 4%; P < .001) and among those with influenza B vs A(H3N2) virus infections (7% vs 0.3%; P < .001). Conclusions: Measurement of antineuraminidase antibodies in addition to antihemagglutinin antibodies may be important in capturing the true influenza infection rates. Abstract : New Zealand's seroepidemiological cohort study found that neuraminidase inhibition assay identified more influenza virus infections than hemagglutination inhibition assay. This result highlights the importance to measure serologically defined infections against not just hemagglutinin but also neuraminidase antigens in future seroepidemiologic cohort studies.